Bidding behavior in asymmetric auctions: An experimental study - Werner Güth; Radosveta Ivanova-Stenzel; Elmar Wolfstetter (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
We review an asymmetric auction experiment. Based on Plum (1992) private valuations of the two bidders are independently drawn from distinct but commonly known distributions, one of which stochastically dominating the other. We test the qualitative properties of that model of asymmetric auctions, in particular whether the weak bidder behaves more aggressively than the strong and then test bidders' preference for first- vs. second-price auctions.
urn:nbn:de:kobv:11-10048752
Keywords: D44; C91; 330; Experiments; Sealed Bid Auctions; Asymmetric Bidders; Private-Independent Values